Geography and its digital dimensions: a cities related discussion to join European inheritage - Gouveia, Luis Borges (2018)
Geography and its digital dimensions: a cities related discussion to join European inheritage We live in a digital world were both people and economy need to learn new rules to adapt to a fast moving environment. However, geography and traditional physical world issues still play a central role. The presentation proposes the discussion of how the digital can change our relation with places, and how geography still needs to be considered as a key factor to any strategy. The implications and transformations for citiesand how they can become central to human organization is proposed to support the discussion to follow the author’s position. Alternative words to stress the importance of remember the past to built a better future.